Legal Protection of Banking Customers in the Perspective of Law 8 of 1999 - Amry Syahputra; Hono Sejati (Journal Research of Social Science, Economics, and Management, 2023)
The use of electronic technology has become prevalent in banking services, offering convenience to customers through internet transaction services. However, this reliance on technology has also exposed vulnerabilities, leading to violations and crimes that result in significant losses for individuals and even the state. Hacker techniques and breaches of bank financial systems have become unavoidable risks. Banks play a crucial role in the financial system, overseeing business transactions and economic activities. Individuals and businesses choose banks as their preferred institutions for depositing funds, conducting transactions, and obtaining capital. Given the importance of banks, legal protection for customers is essential. This research adopts a normative approach, utilizing both statutory and conceptual methods. Secondary data serves as the primary source, and qualitative descriptive analysis is employed. Conclusions are drawn deductively, specifically regarding the topic of Legal Protection of Banking Customers in relation to Law Number 8 of 1999. The findings emphasize the urgency of legal protection for bank customers under the Consumer Protection Law. This law ensures legal certainty for customers by obligating banks to provide correct and honest services, as well as transparent and accurate information about service conditions and guarantees. Banks should collaborate with consumer institutions or other bodies to formulate clauses that meet the needs of all parties without compromising legal certainty. Agreement on the interpretation of relevant clauses is also crucial.